Zebrafish Circadian Clock Entrainment and the Importance of Broad Spectral Light Sensitivity - Steindal, Inga A. Frøland; Whitmore, David (Frontiers in Physiology, 2020)
One of the key defining features of an endogenous circadian clock is that it can be entrained or set to local time. Though a number of cues can perform this role, light is the predominant environmental signal that acts to entrain circadian pacemakers in most species. For the past 20 years, a great deal of work has been performed on the light input pathway in mammals and the role of intrinsically photosensitive retinal ganglion cells (ipRGCs)/melanopsin in detecting and sending light information to the suprachiasmatic nucleus (SCN). In teleost fishes, reptiles and birds, the biology of light sensitivity is more complicated as cells and tissues can be directly light responsive. Non-visual light signalling was described many years ago in the context of seasonal, photoperiodic responses in birds and lizards. In the case of teleosts, in particular the zebrafish model system, not only do peripheral tissues have a circadian pacemaker, but possess clear, direct light sensitivity. A surprisingly wide number of opsin photopigments have been described within these tissues, which may underpin this fundamental ability to respond to light, though no specific functional link for any given opsin yet exists. In this study, we show that zebrafish cells show wide spectral sensitivities, as well as express a number of opsin photopigments – several of which are under direct clock control. Furthermore, we also show that light outside the visual range, both ultraviolet and infrared light, can induce clock genes in zebrafish cells. These same wavelengths can phase shift the clock, except infrared light, which generates no shift even though genes such as per2 and cry1a are induced.